Cognitive complexity of social images revealed by Jewish Israeli adolescents relating to drawings of Jews and Arabs. (5th December 2019) - Teichman, Yona; Stein, Hila; Shechner, Tomer
Abstract: The present study examined age‐related differences among Israeli youth regarding the complexity of their mental images of Jews and Arabs, two groups that are adversaries in the Middle East conflict. The participants, 494 Jewish children and adolescents ranging from 8–16 years old each, drew two human figures, one Jewish and one Arab, and then attributed a forename and a profession to each drawn image. Four complexity variables were scored as follows: image complexity (number of items included in the figure), embellishments (number of items added to the drawing and in the space around the figure), image name, and image profession. Overall, participants depicted members of their in‐group as more complex. However, early adolescence was found to be a critical age at which differences emerged. The findings suggest that introducing complexity to social representations in early adolescence may facilitate prevention of negative associations related to outgroups and enhance intervention to reduce stereotypes, prejudice, and racism.